2018
DOI: 10.1371/journal.pone.0192094
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of randomised controlled trials assessing effectiveness of prosthetic and orthotic interventions

Abstract: BackgroundAssistive products are items which allow older people and people with disabilities to be able to live a healthy, productive and dignified life. It has been estimated that approximately 1.5% of the world’s population need a prosthesis or orthosis.ObjectiveThe objective of this study was to systematically identify and review the evidence from randomized controlled trials assessing effectiveness and cost-effectiveness of prosthetic and orthotic interventions.MethodsLiterature searches, completed in Sept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 247 publications
(269 reference statements)
0
28
0
2
Order By: Relevance
“…Although some present scientific studies do not provide sufficient arguments in order to draw strong conclusions on effectiveness and cost-effectiveness of orthotic devices [8], we sustain the importance of using high quality orthoses in rehabilitation medicine. There are many researches that point out the utility of orthotic intervention in scoliosis, knee deformities and rheumatoid arthritis [9][10][11][12].…”
Section: Discussionmentioning
confidence: 70%
“…Although some present scientific studies do not provide sufficient arguments in order to draw strong conclusions on effectiveness and cost-effectiveness of orthotic devices [8], we sustain the importance of using high quality orthoses in rehabilitation medicine. There are many researches that point out the utility of orthotic intervention in scoliosis, knee deformities and rheumatoid arthritis [9][10][11][12].…”
Section: Discussionmentioning
confidence: 70%
“…Whilst, this study provides a general overview on the breadth of high-level published research which has examined the effectiveness and cost-effectiveness of prosthetic and orthotic provision, further in-depth analysis of the studies identified within this scoping study needs to be completed. Following on from the findings of this scoping study, a systematic review on prosthetic and orthotic interventions has been published [16].…”
Section: Resultsmentioning
confidence: 99%
“…The following 14 databases were searched: Web of Science, Medline, PubMed, CINAHL Plus, EMBASE, SCOPUS, Rehabdata, PsycInfo, ERIC, Education Research Complete, Business Source Complete, IEEE, NIHR and CEA Registry. MeSH headings and free text terms for orthotics and prosthetics were used along with study design categories to capture all research in the area of orthotics and prosthetics (sample search strategy for MEDLINE is provided elsewhere [16].. No language restriction was applied to the search. Searches were adapted for each database and were completed between 22nd and 27th September 2015.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Small sample-size is a common issue in the field of prosthetics, as it is difficult to recruit large participant cohorts from the small limb-absent population. 118 One way to help address this issue is to develop a commonly-agreed framework for reporting participant characteristics, clinical outcomes and the engineering characteristics of the components tested, so that comparisons can be made across studies and the foundations laid for big data approaches. 119 Strengthening the partnerships and collaborations between academic institutions, the prosthetics industry, clinics, hospitals and societies of people with limb absence is important for ensuring research is informed by an understanding of the users' needs, and that the research outputs inform changes in clinical practice.…”
Section: Comparing Prosthetic Components and Intervention Strategiesmentioning
confidence: 99%